PEMASARAN ABON IKAN DI KOTA KENDARI PROPINSI SULAWESI TENGGARA - Roslindah Daeng Siang; Desy Sriwulan; Risfandi Risfandi (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2017)
The purpose of this research is to identify marketing problems, analyze the marketing pattern, and to find out the market map and the direction of the marketing target of abon ikan. This research was conducted by survey method. Methods of collecting data by direct observation and in-depth interviews. The research respondents were producers, traders and consumers of shredded fish products, which were selected by purposive sampling. Data analysis with descriptive methods, using qualitative analysis, namely tracking marketing channels, and market mapping. The results of the study show that the main problem of marketing abon ikan is the availability of raw materials that are not continuous, low production technology, low business capital, production houses do not meet standards, incomplete business licensing, product certificates, training and development of quality human resources are still lacking and the availability of clean water. There are three types of marketing channel patterns, namely from producers to consumers, from producers to the center of Kendari then to consumers, and from producers to traders in Surabaya. Processing businesses cannot yet produce sustainably, the market area is only limited in Kendari City and the surrounding districts in Southeast Sulawesi, so there is still a need to develop a broader market development strategy